2020
DOI: 10.1371/journal.pone.0239988
|View full text |Cite
|
Sign up to set email alerts
|

Are politically diverse Thanksgiving dinners shorter than politically uniform ones?

Abstract: Americans on the political left and right are engaged in a Culture War with one another, one that is often characterized by mutual fear, antipathy, and avoidance. Are there safe havens from the socially straining effects of this Culture War, times and places where Americans of different political stripes gather and put aside their political differences? Previous research (Chen & Rohla, 2018) implied that there might not be insofar as even intimate family gatherings seem to be subject to Culture War tensions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…First, the directionality of the association between familial relationships and parent–child political incongruence remains unclear. In line with previous evidence (Cowan & Baldassarri, 2018; Frimer & Skitka, 2020; Iyengar et al., 2019; Khan, 2019; Kobayashi & Tse, 2022; Lee, 2021; Youth Research Centre, 2019), this study found that parent–child political incongruence may be a common theme initiating and intensifying family conflicts that can in turn worsen familial relationships. Given that this study did not measure changes in perceived political differences with family members from T1 to T2, we mainly examined and discussed the impact of political incongruence on changes in family functionality over a two‐week period.…”
Section: Discussionsupporting
confidence: 90%
“…First, the directionality of the association between familial relationships and parent–child political incongruence remains unclear. In line with previous evidence (Cowan & Baldassarri, 2018; Frimer & Skitka, 2020; Iyengar et al., 2019; Khan, 2019; Kobayashi & Tse, 2022; Lee, 2021; Youth Research Centre, 2019), this study found that parent–child political incongruence may be a common theme initiating and intensifying family conflicts that can in turn worsen familial relationships. Given that this study did not measure changes in perceived political differences with family members from T1 to T2, we mainly examined and discussed the impact of political incongruence on changes in family functionality over a two‐week period.…”
Section: Discussionsupporting
confidence: 90%
“…As noted, a disagreement on importantly held attitudes is potentially threatening and may lead people to double down on their preexisting views. This will generally have negative implications for interactions (Frimer and Skitka, 2020), because, as described below, high-quality interactions often flourish in the presence of curiosity and receptivity to another person's point of view. Itzchakov and DeMarree 10.3389/fpsyg.2022.932413 the speakers feel psychologically safe to share their experiences authentically (e.g., Van Quaquebeke and Felps, 2018;Weinstein et al, 2022).…”
Section: Interpersonal Threatsmentioning
confidence: 99%
“…As noted, a disagreement on importantly held attitudes is potentially threatening and may lead people to double down on their preexisting views. This will generally have negative implications for interactions ( Frimer and Skitka, 2020 ), because, as described below, high-quality interactions often flourish in the presence of curiosity and receptivity to another person’s point of view.…”
Section: Interpersonal Threatsmentioning
confidence: 99%
“… Lee (2021) found that close elections may even “close off” strong tied relationships because Americans are less likely to travel and have shorter Thanksgiving dinners following close elections. Thanksgiving dinners among politically diverse groups are also significantly shorter than those who agree on politics ( Frimer and Skitka 2020 ). These studies are good indicators of a trend of political separation, but their designs do not directly test how political can change social networks overtime.…”
Section: Introductionmentioning
confidence: 99%